In vitro Study of Antioxidant Potentials, and Thrombolytic Activity of the Leaves of Delonix regia (Family: Fabaceae) - Kabir, Mahfuzul; Karim Tipu, Md Fazlul; Islam, Mohammad Ashraful; Shahriar, Saimon; Amin, Al; Khan, Labib; Kabir, Md Alamgir; Chowdhury, Abu Asad (Bangladesh Pharmaceutical Journal, 2023)
This study was conducted to assess the antioxidant potential and thrombolytic activity of the methanolic extract of the Delonix regia leaves and its partitionates. The methanolic extract was partitioned into four fractions (pet ether, dichloromethane, ethyl acetate, and aqueous) according to polarity. These fractions were subjected to further investigation. The antioxidant potential was assessed by two methods one was by using the Folin-Ciocalteu reagent as oxidant and gallic acid as a standard; and another method was the DPPH assay. In Folin-Ciocalteu reagent using method, all fractions showed significant antioxidant potential and the ethyl acetate partitionate showed the highest antioxidant activity at 142.28 mg of GAE/gm of extractives among all. In the DPPH assay, the antioxidant potential was measured compared against BHT, all fractions showed better activity than the BHT and the highest IC50 value was 51.06 μg/mL of dichloromethane partitionate. In thrombolytic activity, streptokinase was the positive control, and water was the negative control. The highest thrombolytic activity was found in petroleum ether partition and methanolic extract and the IC50 value were 47% and 30.65%, respectively. Whereas the IC50 value of streptokinase and water was 64.22% and 15.48% respectively. Bangladesh Pharmaceutical Journal 26(1): 73-78, 2023 (January)